Characterization and properties of palm fiber filled unsaturated polyester composites - Nurul Izza bt Abdul Hamid (School of Materials Engineering, 2011)
This research was to carry out a study on the potential of palm fiber as a filler for unsaturated polyester. The objectives of this research are; a) to study the effect of filler loading and particle size on the properties of palm fiber filled unsaturated polyester composites; b) to study the effect of oleoyl chloride of palm fiber on properties of UP/PF composites; c) to study the effect of 4-Dimethylaminopyridine (DMAP) of palm fiber on properties of UP/PF composites; d) to study the effect treatment with seawater of palm fiber on properties of UP/PF composites.